2015
DOI: 10.3109/17453674.2015.1044389
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes is associated with persistent pain after hip and knee replacement

Abstract: Background and purpose In some patients, for unknown reasons pain persists after joint replacement, especially in the knee. We determined the prevalence of persistent pain following primary hip or knee replacement and its association with disorders of glucose metabolism, metabolic syndrome (MetS), and obesity.Patients and methods The incidence of pain in the operated joint was surveyed 1–2 years after primary hip replacement (74 patients (4 bilateral)) or primary knee replacement (119 patients (19 bilateral)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 26 publications
0
36
0
2
Order By: Relevance
“…Similar to the findings of earlier studies [18][19][20], drug use was more frequent especially when patient BMI exceeded 35 kg/ m 2 . Obese patients report more pain after joint replacement [7,18], which is one possible explanation for this finding. Obesity has also been associated with analgesic use in the general population [30,31].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Similar to the findings of earlier studies [18][19][20], drug use was more frequent especially when patient BMI exceeded 35 kg/ m 2 . Obese patients report more pain after joint replacement [7,18], which is one possible explanation for this finding. Obesity has also been associated with analgesic use in the general population [30,31].…”
Section: Discussionmentioning
confidence: 89%
“…Patients with epilepsy use more opioids in the general population [34], possibly due to a higher prevalence of painful conditions, and we found a similar finding in joint replacement recipients. Interestingly, although diabetes is associated with persistent postoperative pain [7], the disease was not associated with analgesic consumption, especially when their higher BMIs were taken into account [7]. Earlier, controversial results have been reported.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is consistent with our findings of persistent symptoms and greater chance of developing symptomatic OA among those with multiple comorbidities including DM. Another study found a greater likelihood of persistent pain after joint replacement among individuals with DM, but not with metabolic syndrome or obesity [14]. However, in the JoCo OA, the lifetime risk of HOA did not vary substantially by BMI or other demographic features [5].…”
Section: Discussionmentioning
confidence: 93%
“…Gharaibeh et al reported a positive correlation between diabetes and acute kidney injury in patients after THA. In terms of direct orthopaedics complications the following are mentioned: periprosthetic fractures, dislocations, aseptic loosening, persistent pain, revision risk and increased re‐admission rates . Martinez‐Huedo et al report higher rates of mortality in patients with DM vs non‐DM after TKAs and THAs.…”
Section: Impact Of Diabetes On Total Knee Arthroplasty (Tka) and Totamentioning
confidence: 99%